Austin powers, International man of mystery [videorecording (Blu-Ray)] - Roach, Jay; Hurley, Elizabeth, 1965-; York, Michael, 1942-; Rogers, Mimi; Myers, Mike, 1963- (New Line Home Video, 2011)
Frozen in the 60's, secret agent Austin Powers is thawed back into action to once again battle his archenemy Dr. Evil. With his sexy sidekick Ms. Kensington, Austin must stop Dr. Evil's outrageous plot to control the world. But first, this time-warped swinger must get hip quick and discover that there's no free love in the 90's!